(3RHOI cTa GdeeGdc hHjGf GdWQb hGdeSGdcs - (3Ndjd Hf TGgjf GdXGgQj, ZQS GdOjf, jYQa HGHf TGgjf,J (B873 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGaY Ndbg ahb HYV OQLGJ s
(3BNQgG (B:s
(3Je GdcJGH s
(3hQJHg Ydi ebOeI hGKfi YTQ HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B120s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B151 s
Keywords: (3GdJGQjNs